implementasi manajemen resiko terhadap keberlangsungan usaha umkm - Muhammd ridwan (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
ABSTRACT This study aims to analyze several potential risks and strategies to be applied by Buah Reza MSMEs. This research uses qualitative research methodology and data collection techniques in the form of interviews with these business owners. MSMEs Reza Fruit Risks are identified as the most frequent risks and classified as high risk in MSMEs Buah Reza is a risk of decreasing sales, which is quite especially in online ordering, because discounts in it are not always there, The number of existing competitors will cause fewer buyers in Buah Resa MSMEs and the increasingly expensive price of raw materials can cause an increase in the price of goods sold and can cause a decrease in the purchase price of Fruit To minimize the risks that may arise, It is necessary to identify risks and then proceed with analysis and mitigation. One possible method of assistance is through making sure the online ordering platform is presented in a user-friendly manner, improving product quality to provide added value to customers and long-term price agreements.